Istiqāmah dalam Al-Qur’an: Analisis Tematik dan Implikasi Teologis pada QS. al-Ahqāf/46:13 dan QS. Fuṣṣilat/41:30 - Ahmad Furqon Al Mubarok; Irfan Padlian Syah; Abdul Ghofur (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2025)
Istiqāmah is an essential attitude in life. However, it remains a concept that is easy to articulate but difficult to practice consistently among Muslims. This article explores the meaning of istiqāmah in the Qur'an through a thematic interpretation (Tafsīr maudhū‘ī) approach, focusing on two key verses: Surah al-Ahqāf/46:13 and Surah Fuṣṣilat/41:30. In addition, the article discusses the benefits of istiqāmah, including being a means for prayers to be granted, a cause for sustenance, and a source of optimism and self-confidence. The article also outlines steps to actualize istiqāmah, such as purifying intentions, maintaining earnest effort (ikhtiyār), and fostering a righteous social environment. This study employs a qualitative method in the form of library research, using Tafsīr al-Marāghī by Shaykh Aḥmad Muṣṭafā al-Marāghī as the primary source, and Tafsīr Ibn Kathīr, Tafsīr al-Miṣbāḥ, along with several other references as secondary sources. The findings indicate that istiqāmah in the Qur’anic context refers to firmness in faith (‘aqīdah) and consistency in worship without associating partners with Allah. Those who uphold istiqāmah are promised tranquility, inner peace, and the reward of Paradise. These findings highlight the urgency of embodying istiqāmah in the lives of Muslims as a pathway to both spiritual and social success.